The NASA/JPL program in microgravity fundamental physics - Israelsson, U. E.; Lee, M. C. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1998)
The National Aeronautics and Space Administration (NASA) has been supporting research in microgravity low temperature physics for about 20 years. In the last 10 years, the program has seen significant growth in the number of funded investigations and in the breadth of the research activities being pursued. Currently, flight experiments are being performed exclusively on the Space Shuttle. For the future, a cryogenic Space Station facility is being developed by the Jet Propulsion Laboratory and industrial partners to support the microgravity needs of the international scientific community. The facility will be attached to the Japanese Experiments Module`s Exposed Facility and will operate with a 6 month helium cryogen lifetime. Flights of the facility are planned at 2 year intervals starting in 2003 with each flight accommodating multiple scientific experiments. Capabilities, conceptual designs and development plans for the facility are discussed along with a summary of potential near term flight candidate experiments.